COVID-19–Related Stressors, Sex Behaviors, and HIV Status Neutral Care Among Black Men Who Have Sex With Men and Transgender Women in Chicago, USA - Liadh Timmins (JAIDS Journal of Acquired Immune Deficiency Syndromes, 2021)
Background: COVID-19 has disproportionately impacted vulnerable populations, including Black men who have sex with men (BMSM) and transgender women (BTW). We investigated associations of COVID-19 stressors and sex behaviors with pre-exposure prophylaxis (PrEP) and antiretroviral therapy (ART) among BMSM and BTW. Methods: As part of the Neighborhoods and Networks (N2) study, we conducted virtual interviews during peak COVID-19 infectivity in Chicago among BMSM and BTW (April–July 2020). Survey questions included multilevel COVID-19 stressors, sex behaviors, and current PrEP/ART use and access. Poisson regressions were used to examining relationships between COVID-19 stressors, sex behaviors, and PrEP/ART use/access. Results: Among 222 participants, 31.8% of participants not living with HIV reported current PrEP use and 91.8% of participants living with HIV reported ART use during the pandemic. Most (83.3% and 78.2%, respectively) reported similar or easier PrEP and ART access during the pandemic. Physical stress reaction to COVID-19 [adjusted prevalence ratio [aPR] = 2.1; confidence interval (CI): 1.3 to 3.5] and being in close proximity with someone diagnosed with COVID-19 (aPR = 1.7; CI: 1.1 to 2.8) were associated with current PrEP use. Intimate partner violence (aPR = 2.7; CI: 1.0 to 7.2) and losing health insurance (aPR = 3.5; CI: 1.1 to 10.7) were associated with harder ART access. Travel-related financial burden was associated with harder access in PrEP (aPR = 3.2; CI: 1.0 to 10.1) and ART (aPR = 6.2; CI: 1.6 to 24.3). Conclusions: Multiple COVID-19 stressors were found to interfere with PrEP and ART use and access among BMSM and BTW. Contextually relevant strategies (eg, promoting telehealth and decreasing transportation burden) to address COVID-19 stressors and their sequelae should be considered to minimize disruption in HIV biomedical interventions.